NiS2 / Pt composite catalyst coupling prepared azotriazole energetic material, method and system

By using NiS2/Pt composite catalyst in the H-type electrolytic cell for dual electrode coupling reaction, azotriazole energy-containing materials were successfully prepared, which solved the problem of high reaction conditions in the prior art, and achieved a low energy consumption and a simple and controllable preparation process.

CN119710799APending Publication Date: 2025-03-28NORTHWEST UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411843777.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-14
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing azotriazole energy-containing material preparation methods have high reaction conditions and are difficult to achieve industrialization.

Method used

The method of preparing azotriazole-energic materials is used to couple NiS2/Pt composite catalysts. By using copper oxide nanowires as the anode and CC@NiS2/Pt as the cathode in the H-type electrolytic cell, a double-electrode coupling reaction is carried out to generate azotriazole-energic materials.

Benefits of technology

This method avoids the high temperature and toxic heavy metal reactants in traditional synthesis methods. The reaction is carried out at room temperature, the conditions are simple and controllable, and the cathode hydrogen production tank pressure and energy consumption are lower, which solves the problem of high reaction conditions requirements in the existing technology and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710799A_ABST
    Figure CN119710799A_ABST
Patent Text Reader

Abstract

The invention discloses an azotriazole energetic material prepared by coupling a NiS2 / Pt composite catalyst, and a method and a system thereof, and belongs to the technical field of energetic material preparation. According to the method disclosed by the invention, a copper oxide nanowire is used as an anode, CC-coated NiS2 / Pt is used as a cathode, an alkaline solution of 3, 5-diamino-1, 2, 4-triazole is used as a preparation raw material, a dual-electrode coupling reaction is carried out on the basis of an H-type electrolytic bath, and the azotriazole energetic material is produced; according to the method, the defects of a traditional organic preparation method are overcome, the reaction can be carried out at the room temperature, the reaction conditions are simple and controllable, meanwhile, due to the fact that the oxidation reaction has the lower reaction potential compared with OER (1.23 V vs RHE), the cathode hydrogen production tank pressure and energy consumption of a coupling system (HERDATOR) are lower, and the hydrogen production efficiency is improved. The technical problem that industrialization is difficult to achieve due to the fact that an existing preparation method is high in reaction condition requirement is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energetic material preparation, and specifically relates to a NiS 2 / Pt composite catalyst coupling preparation of azotriazole energetic materials and methods and systems. Background Art

[0002] Energetic materials are compounds or mixtures that contain explosive groups or contain oxidants and combustibles, can independently undergo chemical reactions and output energy. Organic energetic materials with high nitrogen content are favored by researchers because of their high-energy bonds of N=N and C=N. Azo compounds and amino compounds are important organic molecules. Due to the unique properties of N=N in azo molecules and the important applications of amines in the industrial production of dyes, drugs and other chemicals, azo compounds have aroused widespread interest in the chemical community. Since triazole derivatives are often more thermodynamically and kinetically stable than similar tetrazole derivatives, research on azoazoles in this field shows great promise for energetic materials.

[0003] However, traditional routes to synthesize azo compounds usually involve high processing temperatures and toxic / heavy metal reactants and are accompanied by many complex reaction synthesis steps. Therefore, the synthesis of high-value azo compounds remains a key challenge. Some researchers have proposed several strategies for the selective synthesis of azo compounds by changing the adsorption / desorption energy of some reaction intermediates and / or active hydrogen on catalysts. However, most of these strategies focus on the modification of catalysts or the use of light of different wavelengths to achieve different product selectivities, which cannot fundamentally solve the problems of complex synthesis of azo materials, high energy consumption, and low yield.

[0004] In summary, a new method for preparing energetic materials capable of coupling azotriazole is urgently needed. Summary of the invention

[0005] The object of the present invention is to provide a NiS 2 The invention discloses azotriazole energetic material, method and system prepared by coupling with Pt composite catalyst, which is used to solve the technical problem that the existing preparation method has high requirements on reaction conditions and is difficult to realize industrialization.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a NiS 2 The method for preparing azotriazole energetic material by coupling a / Pt composite catalyst comprises the following steps: The alkaline solution of 3,5-diamino-1,2,4-triazole and pure alkali solution were placed in the anode area and cathode area of ​​the H-type electrolytic cell respectively, the copper oxide nanowires were placed in the alkaline solution of 3,5-diamino-1,2,4-triazole, and the CC@NiS2 / Pt is placed in pure alkali solution, followed by a double electrode coupling reaction to generate azotriazole energetic materials.

[0007] Furthermore, the alkaline solution of 3,5-diamino-1,2,4-triazole is obtained by mixing 3,5-diamino-1,2,4-triazole and alkali solution; the alkali solution is a NaOH solution or a KOH solution; and the concentration of 3,5-diamino-1,2,4-triazole in the alkaline solution of 3,5-diamino-1,2,4-triazole is 0.02-0.32 mol / L.

[0008] Furthermore, the pure alkali solution is a NaOH solution or a KOH solution; the concentration of the pure alkali solution is 1-3 mol / L.

[0009] Furthermore, the current density of the two-electrode coupling reaction is 5-30 mA·cm -2 , time is 1~2 h.

[0010] Furthermore, the CC@NiS 2 The preparation method of / Pt comprises the following steps: NiCl 2 6H 2 O, water, NH 4 F and urea are mixed to obtain a mixed solution; the conductive carrier carbon cloth is added to the mixed solution for hydrothermal reaction to obtain CC loaded Ni(OH) 2 Nanosheets; CC loaded with Ni(OH) 2 The nanosheets react with sulfur powder in a heating device to obtain CC-loaded NiS 2 Nanosheets; Loading CC with NiS 2 After the nanosheets were washed and dried in sequence, the deposition reaction was carried out by cyclic voltammetry using Pt ion electrolyte in a three-electrode system to obtain CC@NiS 2 / Pt.

[0011] Furthermore, the NiCl 2 6H 2 O, water, NH 4 The dosage ratio of F and urea is (1.3~1.8)mmol:15mL:(2~4)mmol:(5.5~7.5)mmol; The area of ​​the conductive carrier carbon cloth is 2~6cm 2 ; The temperature of the hydrothermal reaction is 180~220℃ and the time is 4~6h.

[0012] Furthermore, the CC is loaded with Ni(OH) 2The nanosheets react with sulfur powder in a heating device to obtain CC-loaded NiS 2 The specific steps of nanosheets are: 0.2~1.0g of sulfur powder was placed upstream of the tube furnace, and the obtained CC was loaded with Ni(OH) 2 The nanosheets were placed in the downstream of the tube furnace and heated at 5-10 °C min under the protection of Ar gas. -1 The temperature was raised to 150-300 °C at a heating rate of 4-6 h to obtain CC-loaded NiS 2 Nanosheets.

[0013] Furthermore, the Pt ion electrolyte is obtained by mixing chloroplatinic acid and KOH solution; the volume concentration of chloroplatinic acid in the Pt ion electrolyte is 10-30 mg mL -1 The three motors in the three-electrode system include CC@NiS 2 As the working electrode, graphite rod as the counter electrode and Hg / HgO as the reference electrode.

[0014] The invention also discloses an azotriazole energetic material prepared by the preparation method.

[0015] The invention also discloses a coupled electrolysis system for realizing the steps of the preparation method.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a NiS 2 / Pt composite catalyst coupling method for preparing azotriazole energetic materials, by using copper oxide nanowires as anode, CC@NiS 2 / Pt is used as the cathode, an alkaline solution of 3,5-diamino-1,2,4-triazole is used as the preparation raw material, and a double-electrode coupling reaction is carried out on the basis of an H-type electrolytic cell to produce an azotriazole energetic material; this method avoids the defects of traditional organic preparation methods, uses green electrons as oxidants at the anode to prepare 5,5'-diamino-3,3'-azo-1H-1,2,4-triazole energetic materials, and there is no need to separate the by-products produced by the oxidant, the reaction can be carried out at room temperature, and the reaction conditions are simple and controllable. At the same time, since the oxidation reaction has a lower reaction potential than OER (1.23 V vs RHE), the cathode hydrogen production cell pressure and energy consumption of the coupled system (HER||DATOR) are lower, which solves the technical problem that the existing preparation method has high reaction conditions and is difficult to achieve industrialization, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 NiS 2Schematic diagram of the method for preparing azotriazole energetic materials by coupling / Pt composite catalyst; Figure 2 CC@NiS in Example 1 of the present invention 2 Schematic diagram of the scanning electron microscope characterization results of / Pt; Figure 3 NiS in Example 1 of the present invention 2 Schematic diagram of transmission electron microscopy characterization results of / Pt; Figure 4 NiS in Example 1 of the present invention 2 / Schematic diagram of element mapping results of Pt; Among them: a-Ni element TEM map; b-S element mapping map; c-Pt element mapping map; d-S element mapping map; Figure 5 This is a schematic diagram of the scanning electron microscope characterization results of the copper oxide nanowires in Example 1 of the present invention; Figure 6 CC@NiS in Example 1 of the present invention 2 and X-ray diffraction patterns of copper oxide nanowires; Among them: a-CC@NiS 2 ; b-copper oxide nanowires; Figure 7 This is the alkaline HER performance test curve of the cathode catalyst in Example 1 of the present invention; Among them: a-CC@NiS 2 / Pt, commercial Pt / C electrodes and CC@NiS 2 LSV curve; b-Tafel curve; Figure 8 The coupling system and LSV curve of the alkaline HER and the electrosynthesized 5,5'-diamino-3,3'-azo-1H-1,2,4-triazole energetic material in Example 1 of the present invention; Fig. 9 The nuclear magnetic resonance of the electrosynthesized 5,5'-diamino-3,3'-azo-1H-1,2,4-triazole energetic material in Example 1 of the present invention 13 C spectrum. DETAILED DESCRIPTION

[0018] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0019] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0020] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0021] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0022] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0023] The present invention provides a NiS 2 The method for preparing azotriazole energetic material by coupling a / Pt composite catalyst comprises the following steps: The copper oxide nanowires were placed in a NaOH solution containing 3,5-diamino-1,2,4-triazole. 2 / Pt is placed in pure alkali solution and combined with an H-type electrolyzer device to form a coupled electrolysis system to carry out a double-electrode coupling reaction to achieve anode electrosynthesis (azotriazole energetic material) DAAT EMs and cathode low-energy hydrogen production.

[0024] Preferably, the alkaline solution of 3,5-diamino-1,2,4-triazole is obtained by mixing 3,5-diamino-1,2,4-triazole and alkali solution; the alkali solution is a NaOH solution or a KOH solution; and the concentration of 3,5-diamino-1,2,4-triazole in the alkaline solution of 3,5-diamino-1,2,4-triazole is 0.02-0.32 mol / L.

[0025] Preferably, the pure alkali solution is a NaOH solution or a KOH solution; the concentration of the pure alkali solution is 1-3 mol / L.

[0026] Preferably, the current density of the two-electrode coupling reaction is 5-30 mA·cm -2 , time is 1~2 h.

[0027] During the preparation process, the electrode reaction processes of the cathode and anode are: Cathode reaction: (Volmer); (Heyrovsky); Anode reaction: .

[0028] Wherein, the preparation method of copper oxide nanowires is: The foamed copper is soaked in an alkaline solution containing an oxidant for a period of time to generate copper hydroxide nanowires, which are then calcined at high temperature in air to obtain pure phase copper oxide nanowires; wherein the oxidant is one of sodium persulfate and ammonium persulfate, the soaking time can be 30-60 minutes, the calcination temperature is 200-400°C, and the calcination time is 2-4 hours.

[0029] CC@NiS 2 The preparation method of / Pt is: Step 1: Weigh a certain amount of NiCl 2 6H 2 O was dissolved in 15 mL of deionized water and a certain amount of NH 4 F and urea to obtain a mixed solution; Step 2: Add the cleaned conductive carrier carbon cloth (CC) to the mixed aqueous solution obtained in step 1 for hydrothermal reaction to obtain CC loaded Ni(OH) 2 Nanosheets; Step 3: Weigh a certain amount of sulfur powder and place it upstream of the tube furnace. 2 The nanosheets were placed in the downstream of the tube furnace and heated to a certain temperature at a fixed heating rate under the protection of high-purity Ar gas. After a certain reaction time, CC-loaded NiS was obtained. 2 Nanosheets (CC@NiS 2 ); Step 4: The reacted CC@NiS 2 It was rinsed with water and ethanol and dried at 60 °C for 1.0 h for the subsequent deposition of Pt particles; Step 5: Different volumes of chloroplatinic acid were added to 1.0 M KOH solution to prepare Pt ion electrolyte; then, Pt deposition reaction was carried out by cyclic voltammetry in a three-electrode system to prepare CC@NiS 2 / Pt, wherein by controlling the amount of different Pt solutions and the cyclic voltammetry time, nickel disulfide nanosheets loaded with Pt nanoparticles of different concentrations can be obtained.

[0030] Preferably, in step 1, NiCl2 6H 2 O, water, NH 4 The dosage ratio of F and urea is (1.3~1.8) mmol:15mL: (2~4) mmol: (5.5~7.5) mmol.

[0031] Preferably, in step 2, the carbon cloth is cleaned with acetone and ethanol, and the area of ​​the carbon cloth is 2-6 cm 2 The hydrothermal reaction temperature is 180~220℃ and the reaction time is 4~6h. Within this temperature and time range, the reaction can effectively regulate Ni(OH) 2 The size of nanosheets on the CC surface and their surface coverage uniformity.

[0032] Preferably, in step 3, the mass of the sulfur powder used is 0.2-1.0 g, and the heating rate of the tubular furnace is 5-10°C min -1 , the reaction temperature is 150~300℃, and the reaction time is 4~6h.

[0033] Preferably, in step 5, the volume concentration of chloroplatinic acid in the electrolyte is 10-30 mg mL -1 The volume dosage is 0.1~3mL; the purpose of controlling the amount of Pt nanoparticles loading is achieved by controlling the volume dosage of chloroplatinic acid, and the catalytic activity is better within the range of chloroplatinic acid content; the electrodes are CC@NiS 2 (working electrode), graphite rod (counter electrode) and Hg / HgO (reference electrode); the cyclic voltammetry test voltage range is -0.5~0 V vs. RHE, which is the active range of electrodeposited Pt nanoparticles; the cyclic voltammetry test time is 1000~4000s. Outside this test range, the optimal alkaline HER activity cannot be achieved due to too little or too much electrodeposited Pt; the cyclic voltammetry rate in step 4 is 5~10mV s -1 .

[0034] The following formula shows the reaction process of the existing traditional DAAT EMs preparation method: ; It can be seen that the traditional preparation method requires at least three steps of chemical synthesis and the participation of oxidants such as acetic anhydride and potassium permanganate. In addition, the high temperature (~190°C) reaction conditions greatly increase the safety risks of the preparation process and the by-product metal salts produced will cause waste of raw materials.

[0035] like Figure 1As shown, the method of the present invention aims at the shortcomings in the synthesis process of traditional azo organic energetic materials, and develops a green and mild electrochemical method for synthesizing azo energetic materials; the new system can simultaneously carry out green electrosynthesis of 5,5'-diamino-3,3'-azo-1H-1,2,4-triazole energetic materials at room temperature; the process has a lower reaction cell voltage, which greatly reduces energy consumption compared to traditional synthesis steps; therefore, the coupled system of HER and electro-oxidation synthesis of DAAT EMs shows lower energy consumption.

[0036] By comparing with the above-mentioned existing traditional preparation methods, it can be seen that the preparation scheme provided by the embodiment of the present invention avoids the defects of the traditional organic preparation method, uses green electrons as oxidants at the anode to prepare 5,5'-diamino-3,3'-azo-1H-1,2,4-triazole energetic materials, and there is no need to separate the by-products produced by the oxidant, and the reaction can be carried out at room temperature.

[0037] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0038] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0039] Example 1 A NiS 2 The method for preparing azotriazole energetic material by coupling a / Pt composite catalyst comprises the following steps: S1: The copper foam was immersed in a 1 mol / L NaOH solution containing 1.48 g of sodium persulfate for 30 min to generate copper hydroxide nanowires, which were then calcined at 200 °C in air for 2 h to obtain pure copper oxide nanowires; S2: weigh 1.3 mmol of NiCl 2 6H 2 O was dissolved in 15 mL of deionized water and 2 mmol of NH 4 F and 5.5mmol urea to obtain a mixed solution; S3: Add the mixed solution obtained in S2 to the cleaned conductive carrier carbon cloth (CC, 1*2 cm2 )After hydrothermal reaction at 180℃ for 12h, CC loaded Ni(OH) 2 Nanosheets; S4: Weigh 0.2 g of sulfur powder and place it upstream of the tube furnace. Load Ni(OH) 2 The nanosheets were placed in the downstream of the tube furnace and heated at a rate of 5 °C min under the protection of high-purity Ar gas. -1 After heating to 150℃ and reacting for 4h, CC loaded NiS was obtained. 2 Nanosheets (CC@NiS 2 ); S5: The reacted CC@NiS 2 The system was rinsed with water and ethanol and dried at 60 °C for 1.0 h for the subsequent deposition of Pt particles; S6: 0.1 mL 10 mg mL -1 Chloroplatinic acid was added to 1.0 M KOH solution to prepare Pt ion electrolyte; then, Pt deposition reaction was carried out by cyclic voltammetry in a three-electrode system, with the potential interval set to -0.5~0 Vs. RHE, and the cyclic voltammetry test was performed for 1000 s to prepare CC@NiS 2 / Pt; S7: In the H-type electrolytic cell, the cathode electrode is CC@NiS 2 / Pt, the electrolyte was 1.0 M KOH; the anode electrode was the prepared copper oxide nanowires, 1.0 M KOH was used as the electrolyte, 0.02 mol / L 3,5-diamino-1,2,4-triazole (DAT) was added to the anode reaction solution as a reactant; at 5 mA cm -2 Azotriazole energetic materials (DAAT EMs) were obtained after double electrode coupling reaction at a current density of 1 h.

[0040] Example 2 A NiS 2 The method for preparing azotriazole energetic material by coupling a / Pt composite catalyst comprises the following steps: S1: The copper foam was immersed in a 2 mol / L KOH solution containing 1.48 g ammonium persulfate for 45 min to generate copper hydroxide nanowires, which were then calcined at 300 °C in air for 3 h to obtain pure copper oxide nanowires; S2: Weigh 1.5 mmol of NiCl 2 6H 2 O was dissolved in 15 mL of deionized water and 3 mmol of NH 4 F and 6.5mmol urea to obtain a mixed solution; S3: Add the mixed solution obtained in S2 to the cleaned conductive carrier carbon cloth (CC, 2*2 cm 2 )After hydrothermal reaction at 200℃ for 18h, CC loaded Ni(OH) 2 Nanosheets; S4: Weigh 0.6 g of sulfur powder and place it upstream of the tube furnace. Load the obtained CC with Ni(OH) 2 The nanosheets were placed in the downstream of the tube furnace and heated at a rate of 8 °C min under the protection of high-purity Ar gas. -1 After heating to 220℃ and reacting for 5h, CC loaded NiS 2 Nanosheets (CC@NiS 2 ); S5: The reacted CC@NiS 2 The system was rinsed with water and ethanol and dried at 60 °C for 1.0 h for the subsequent deposition of Pt particles; S6: 1.0 mL 20 mg mL -1 Chloroplatinic acid was added to 1.0 M KOH solution to prepare Pt ion electrolyte. Then, Pt deposition reaction was carried out by cyclic voltammetry under a three-electrode system, and the potential range was set to -0.5~0 Vs. RHE. The cyclic voltammetry test was performed for 3000 s to prepare CC@NiS 2 / Pt; S7: In the H-type electrolytic cell, the cathode electrode is CC@NiS 2 / Pt, the electrolyte was 1.0 M KOH; the anode electrode was the prepared copper oxide nanowires, 1.0 M KOH was used as the electrolyte, 0.08 mol / L 3,5-diamino-1,2,4-triazole (DAT) was added to the anode reaction solution as a reactant; at 8 mA cm -2 After 2 h of double electrode coupling reaction at a current density of 40,000 nm, azotriazole energetic materials (DAAT EMs) were obtained.

[0041] Example 3 A NiS 2 The method for preparing azotriazole energetic material by coupling a / Pt composite catalyst comprises the following steps: S1: The copper foam was immersed in a 3 mol / L NaOH solution containing 1.48 g sodium persulfate for 60 min to generate copper hydroxide nanowires, which were then calcined at 400 °C in air for 4 h to obtain pure copper oxide nanowires; S2: weigh 1.8 mmol of NiCl 2 6H 2 O was dissolved in 15 mL of deionized water and 4 mmol of NH 4 F and 7.5mmol urea to obtain a mixed solution; S3: Add the mixed solution obtained in S2 to the cleaned conductive carrier carbon cloth (CC, 2*3cm 2 )After hydrothermal reaction at 220℃ for 24h, CC loaded Ni(OH) 2 Nanosheets; S4: Weigh 1.0 g of sulfur powder and place it upstream of the tube furnace. Load the obtained CC with Ni(OH) 2 The nanosheets were placed in the downstream of the tube furnace and heated at a rate of 10 °C min under the protection of high-purity Ar gas. -1 After heating to 300℃ and reacting for 6h, CC loaded NiS was obtained. 2 Nanosheets (CC@NiS 2 ); S5: The reacted CC@NiS 2 The system was rinsed with water and ethanol and dried at 60 °C for 1.0 h for the subsequent deposition of Pt particles; S6: 3.0mL 30 mg mL -1 Chloroplatinic acid was added to 1.0 M KOH solution to prepare Pt ion electrolyte. Then, Pt deposition reaction was carried out by cyclic voltammetry in a three-electrode system, with the potential interval set to -0.5~0 Vs. RHE. The cyclic voltammetry test was performed for 4000 s to prepare CC@NiS 2 / Pt; S7: In the H-type electrolytic cell, the cathode electrode is CC@NiS 2 / Pt, the electrolyte was 1.0 M KOH; the anode electrode was the prepared copper oxide nanowires, 1.0 M KOH was used as the electrolyte, 0.32 mol / L 3,5-diamino-1,2,4-triazole (DAT) was added to the anode reaction solution as a reactant; at 10 mA cm -2 After 2 h of double electrode coupling reaction at a current density of 40,000 nm, azotriazole energetic materials (DAAT EMs) were obtained.

[0042] Example 4 A NiS 2 The method for preparing azotriazole energetic material by coupling a / Pt composite catalyst comprises the following steps: S1: The copper foam was immersed in a 3 mol / L KOH solution containing 1.48 g ammonium persulfate for 45 min to generate copper hydroxide nanowires, which were then calcined at 300 °C in air for 2 h to obtain pure copper oxide nanowires; S2: Weigh 1.5 mmol of NiCl 2 6H 2 O was dissolved in 15 mL of deionized water and 3.5 mmol NH 4F and 7.0mmol urea to obtain a mixed solution; S3: Add the mixed solution obtained in S2 to the cleaned conductive carrier carbon cloth (CC, 1*1cm 2 )After hydrothermal reaction at 260℃ for 18h, CC loaded Ni(OH) 2 Nanosheets; S4: Weigh 0.7 g of sulfur powder and place it upstream of the tube furnace. Load Ni(OH) 2 The nanosheets were placed in the downstream of the tube furnace and heated at a rate of 6 °C min under the protection of high-purity Ar gas. -1 After heating to 240℃ and reacting for 5h, CC loaded NiS 2 Nanosheets (CC@NiS 2 ); S5: The reacted CC@NiS 2 The system was rinsed with water and ethanol and dried at 60 °C for 1.0 h for the subsequent deposition of Pt particles; S6: 2.4 mL of 25 mg mL -1 Chloroplatinic acid was added to 1.0 M KOH solution to prepare Pt ion electrolyte. Then, Pt deposition reaction was carried out by cyclic voltammetry under a three-electrode system, and the potential range was set to -0.5~0 Vs. RHE. The cyclic voltammetry test was performed for 2500 s to prepare CC@NiS 2 / Pt; S7: In the H-type electrolytic cell, the cathode electrode is CC@NiS 2 / Pt, the electrolyte was 1.0 M KOH; the anode electrode was the prepared copper oxide nanowires, 1.0 M KOH was used as the electrolyte, 0.2 mol / L 3,5-diamino-1,2,4-triazole (DAT) was added to the anode reaction solution as a reactant; at 8 mA cm -2 After 1.5 h of double electrode coupling reaction at a current density of 40,000 nm, azotriazole energetic materials (DAAT EMs) were obtained.

[0043] Example 5 A NiS 2 The method for preparing azotriazole energetic material by coupling a / Pt composite catalyst comprises the following steps: S1: The copper foam was immersed in a 1 mol / L KOH solution containing 1.48 g of sodium persulfate for 60 min to generate copper hydroxide nanowires, and then pure copper oxide nanowires were obtained by calcining at 300 °C in air for 4 h; S2: weigh 1.6mmol NiCl 2 6H 2 O was dissolved in 15 mL of deionized water and 4 mmol NH4 F and 7.5mmol urea to obtain a mixed solution; S3: Add the mixed solution obtained in S2 to the cleaned conductive carrier carbon cloth (CC, 2*2cm 2 )After hydrothermal reaction at 220℃ for 18h, CC loaded Ni(OH) 2 Nanosheets; S4: Weigh 0.8 g of sulfur powder and place it upstream of the tube furnace. Load the obtained CC with Ni(OH) 2 The nanosheets were placed in the downstream of the tube furnace and heated at a rate of 8 °C min under the protection of high-purity Ar gas. -1 After heating to 230℃ and reacting for 4h, CC loaded NiS 2 Nanosheets (CC@NiS 2 ); S5: The reacted CC@NiS 2 The system was rinsed with water and ethanol and dried at 60 °C for 1.0 h for the subsequent deposition of Pt particles; S6: 2.2 mL of 15 mg mL -1 Chloroplatinic acid was added to 1.0 M KOH solution to prepare Pt ion electrolyte. Then, Pt deposition reaction was carried out by cyclic voltammetry under a three-electrode system, and the potential range was set to -0.5~0 Vs. RHE. The cyclic voltammetry test was performed for 3000 s to prepare CC@NiS 2 / Pt; S7: In the H-type electrolytic cell, the cathode electrode is CC@NiS 2 / Pt, the electrolyte was 1.0 M KOH; the anode electrode was the prepared copper oxide nanowires, 1.0 M KOH was used as the electrolyte, 0.32 mol / L 3,5-diamino-1,2,4-triazole (DAT) was added to the anode reaction solution as a reactant; at 10 mA cm -2 After 2 h of double electrode coupling reaction at a current density of 40,000 nm, azotriazole energetic materials (DAAT EMs) were obtained.

[0044] Example 6 A NiS 2 The method for preparing azotriazole energetic material by coupling a / Pt composite catalyst comprises the following steps: S1: The copper foam was immersed in a 2 mol / L NaOH solution containing 1.48 g of ammonium persulfate for 60 min to generate copper hydroxide nanowires, which were then calcined at 300 °C in air for 4 h to obtain pure copper oxide nanowires; S2: weigh 1.8 mmol of NiCl 2 6H 2O was dissolved in 15 mL of deionized water and 3 mmol NH 4 F and 6.5mmol urea to obtain a mixed solution; S3: Add the mixed solution obtained in S2 to the cleaned conductive carrier carbon cloth (CC, 2*3cm 2 )After hydrothermal reaction at 200℃ for 24h, CC loaded Ni(OH) 2 Nanosheets; S4: Weigh 0.5 g of sulfur powder and place it upstream of the tube furnace. Load the obtained CC with Ni(OH) 2 The nanosheets were placed in the downstream of the tube furnace and heated at a rate of 10 °C min under the protection of high-purity Ar gas. -1 After heating to 280℃ and reacting for 6h, CC loaded NiS 2 Nanosheets (CC@NiS 2 ); S5: The reacted CC@NiS 2 The system was rinsed with water and ethanol and dried at 60 °C for 1.0 h for the subsequent deposition of Pt particles; S6: 0.8 mL 10 mg mL -1 Chloroplatinic acid was added to 1.0 M KOH solution to prepare Pt ion electrolyte. Then, Pt deposition reaction was carried out by cyclic voltammetry under a three-electrode system, and the potential range was set to -0.5~0 Vs. RHE. The cyclic voltammetry test was performed for 3000 s to prepare CC@NiS 2 / Pt; S7: In the H-type electrolytic cell, the cathode electrode is CC@NiS 2 / Pt, the electrolyte was 1.0 M KOH; the anode electrode was the prepared copper oxide nanowires, 1.0 M KOH was used as the electrolyte, 0.25 mol / L 3,5-diamino-1,2,4-triazole (DAT) was added to the anode reaction solution as a reactant; at 5 mA cm -2 After 2 h of double electrode coupling reaction at a current density of 40,000 nm, azotriazole energetic materials (DAAT EMs) were obtained.

[0045] Figure 2 CC@NiS in Example 1 of the present invention 2 Schematic diagram of the scanning electron microscope characterization results of / Pt, where NiS 2 Evenly grown on the CC surface, some Pt ​​particles can be seen evenly attached to NiS 2 Surface, no large area aggregation.

[0046] Figure 3 NiS in Example 1 of the present invention 2Schematic diagram of the transmission electron microscopy characterization results of / Pt. The lens image clearly shows that the black spots of Pt nanoparticles are uniformly loaded on NiS 2 After the nanosheets are loaded with Pt particles, CC@NiS 2 The original nanosheet structure can still be maintained, proving that the catalyst was successfully prepared and has a certain mechanical stability.

[0047] Figure 4 NiS in Example 1 of the present invention 2 Schematic diagram of the element mapping results of Pt. It can be seen that the Pt element is evenly distributed in NiS 2 The surface of the nanosheets further illustrates that the Pt nanoparticles are uniformly loaded on the NiS 2 surface; at the same time, it also shows that Ni and S elements are evenly distributed on the surface of the nanosheets without the introduction of other elements.

[0048] Figure 5 This is a schematic diagram of the scanning electron microscope characterization results of the copper oxide nanowires in Example 1 of the present invention. It can be clearly seen that the copper oxide is in the form of nanowires and is evenly attached to the surface of the foamed copper, proving the three-dimensional structure of the copper oxide anode.

[0049] Figure 6 CC@NiS in Example 1 of the present invention 2 and X-ray diffraction patterns of copper oxide nanowires, Figure 6 (a) is CC@NiS 2 X-ray diffraction pattern of CC@NiS 2 The diffraction peaks of NiS 2 The standard card (JCPDS No. 73-0574) is consistent with NiS 2 It is a pure phase substance without other impurities. The broad peak at 21° is the signal of CC conductive carbon substrate; Figure 6 (b) is the X-ray diffraction pattern of the anode catalyst copper oxide nanowire catalyst, and the peaks at 43°, 50° and 74° are the signals of the foam copper substrate. The diffraction peaks at 35°, 39° and 48° correspond to the black copper oxide (JCPDS No. 45-0937); the diffraction peaks at 36°, 42° and 61° correspond to the cubic copper oxide (JCPDS No. 78-0428), indicating that the copper oxide nanowires prepared on the foam copper substrate are composed of these two copper oxide crystal forms.

[0050] Figure 7 is the alkaline HER performance test curve of the cathode catalyst in Example 1 of the present invention, Figure 7 (a) is CC@NiS 2 、CC@NiS 2LSV curves of alkaline HER of Pt / C and commercial Pt / C electrodes. The lower the overpotential of the curve, the higher the HER catalytic activity. It can be seen that after Pt loading, the performance has been significantly improved compared with that before loading. 2 / Pt shows excellent HER performance. The linear scan curve (LSV) curve fitting shows that CC@NiS 2 / Pt and the Tafel slope of commercial Pt / C electrodes, Figure 7 CC@NiS shown in (b) 2 The Tafel slope of Pt is 33 mV dec -1 Much lower than Pt / C (116.07 mV dec -1 ), indicating that the participation of Pt increases the surface / interface reaction kinetics rate before loading, thereby increasing the HER reaction rate. 2 In the heterostructure of Si / Pt, more active sites are exposed, thereby improving the alkaline HER activity.

[0051] Figure 8 The coupling system and LSV curve of alkaline HER and electrosynthesized 5,5'-diamino-3,3'-azo-1H-1,2,4-triazole energetic material in Example 1 of the present invention, the anode and cathode are respectively copper foam loaded copper oxide nanowires and CC@NiS 2 / Pt; the anode and cathode electrolytes were DAT+1.0 MKOH and 1.0 M KOH, respectively, and the cathode and cathode electrolytes were separated by an anion exchange membrane; at 10 mA / cm 2 Under current, the cell voltage of traditional water electrolysis for hydrogen production is 1.63 V; after preparing DAAT EMs by DAT electrooxidation azotization reaction instead of OER and building a coupling system with HER, the cell voltage is reduced to 0.96 V, which is 670 mV lower than the traditional water electrolysis for hydrogen production, significantly reducing the voltage and energy consumption of the hydrogen production cell.

[0052] Fig. 9 The nuclear magnetic resonance of the electrosynthesized 5,5'-diamino-3,3'-azo-1H-1,2,4-triazole energetic material in Example 1 of the present invention 13 C spectrum, the anolyte after the coupling system test was adjusted to neutral pH with sulfuric acid, stirred at 100 ° C for 30 minutes and then hot filtered. Because 5,5'-diamino-3,3'-azo-1H-1,2,4-triazole is insoluble in methanol, chloroform, toluene, DMSO, and DMF, and is only slightly soluble in water at high temperature, impurities were removed by heating and filtering. The filtered material was dried in a vacuum oven for 12 hours to obtain a dark red powder. 13C NMR characterization; the chemical shifts at 168.37 ppm and 171.24 ppm correspond to -C-NH of 5,5'-diamino-3,3'-azo-1H-1,2,4-triazole structure, respectively. 2 and -CN=N- bonds, proving that 5,5'-diamino-3,3'-azo-1H-1,2,4-triazole energetic materials were successfully synthesized by green electrochemical methods. Therefore, it is verified that the coupling system of the present invention realizes the simultaneous green electrosynthesis of DAAT EMs and low-energy hydrogen production, effectively improving the energy consumption required for hydrogen production and safely synthesizing organic energetic materials.

[0053] The present invention successfully introduced the 3,5-diamino-1,2,4-triazole oxidation reaction (DATOR) into the overall water splitting system, providing a new strategy for energy-saving hydrogen production coupled with green electrosynthesis of organic energetic materials. The coupled system (HER||DATOR) can provide 10 mA cm at a voltage of 0.96 V. -2 The current density was high and the co-production of hydrogen and DAAT EMs was achieved, which reduced the energy loss by 670 mV compared with the traditional OWS system. 2 / Pt has good HER catalytic properties. In addition, the anode of the coupled system successfully realized the green electrosynthesis of DAAT EMs, avoiding the dangerous synthesis conditions of traditional synthesis methods. This study provides a new idea for anodic oxidation reaction to replace OER.

[0054] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing azotriazole energetic materials by coupling NiS2 / Pt composite catalyst, characterized in that: The following steps are involved: The alkaline solution of 3,5-diamino-1,2,4-triazole and the pure alkali solution are placed in the anode area and cathode area of ​​the H-type electrolytic cell respectively, the copper oxide nanowires are placed in the alkaline solution of 3,5-diamino-1,2,4-triazole, and the CC@NiS2 / Pt is placed in the pure alkali solution, followed by a double electrode coupling reaction to generate azotriazole energetic material.

2. The method for preparing azotriazole energetic material by coupling NiS2 / Pt composite catalyst according to claim 1, characterized in that: The alkaline solution of 3,5-diamino-1,2,4-triazole is obtained by mixing 3,5-diamino-1,2,4-triazole and alkaline solution; the alkaline solution is a NaOH solution or a KOH solution; and the concentration of 3,5-diamino-1,2,4-triazole in the alkaline solution of 3,5-diamino-1,2,4-triazole is 0.02-0.32 mol / L.

3. The method for preparing azotriazole energetic material by coupling NiS2 / Pt composite catalyst according to claim 1, characterized in that: The pure alkali solution is a NaOH solution or a KOH solution; the concentration of the pure alkali solution is 1-3 mol / L.

4. The method for preparing azotriazole energetic material by coupling NiS2 / Pt composite catalyst according to claim 1, characterized in that: The current density of the two-electrode coupling reaction is 5-30 mA·cm -2 , time is 1~2 h.

5. The method for preparing azotriazole energetic material by coupling NiS2 / Pt composite catalyst according to claim 1, characterized in that: The preparation method of CC@NiS2 / Pt comprises the following steps: NiCl2 6H2O, water, NH4F and urea are mixed to obtain a mixed solution; a conductive carrier carbon cloth is added to the mixed solution for hydrothermal reaction to obtain CC-loaded Ni(OH)2 nanosheets; The CC-loaded Ni(OH)2 nanosheets and sulfur powder are reacted in a heating device to obtain CC-loaded NiS2 nanosheets; After the CC-loaded NiS2 nanosheets were sequentially eluted and dried, a deposition reaction was carried out using a Pt ion electrolyte by cyclic voltammetry in a three-electrode system to obtain CC@NiS2 / Pt.

6. The method for preparing azotriazole energetic material by coupling NiS2 / Pt composite catalyst according to claim 5, characterized in that: The dosage ratio of NiCl2 6H2O, water, NH4F and urea is (1.3-1.8) mmol:15 mL: (2-4) mmol: (5.5-7.5) mmol; The area of ​​the conductive carrier carbon cloth is 2~6cm 2 ; The temperature of the hydrothermal reaction is 180~220℃ and the time is 4~6h.

7. The method for preparing azotriazole energetic materials by coupling NiS2 / Pt composite catalyst according to claim 5, characterized in that: The specific steps of reacting CC-loaded Ni(OH)2 nanosheets with sulfur powder in a heating device to obtain CC-loaded NiS2 nanosheets are as follows: 0.2-1.0 g of sulfur powder was placed in the upstream of the tube furnace, and the obtained CC-loaded Ni(OH)2 nanosheets were placed in the downstream of the tube furnace. Under the protection of Ar gas, the mixture was heated at 5-10 °C min -1 The temperature was raised to 150-300 °C at a heating rate of 4-6 h to obtain CC-loaded NiS2 nanosheets.

8. The method for preparing azotriazole energetic material by coupling NiS2 / Pt composite catalyst according to claim 5, characterized in that: The Pt ion electrolyte is obtained by mixing chloroplatinic acid and KOH solution; the volume concentration of chloroplatinic acid in the Pt ion electrolyte is 10-30 mg mL -1 ; The three electrodes in the three-electrode system include CC@NiS2 as the working electrode, a graphite rod as the counter electrode and Hg / HgO as the reference electrode.

9. An azotriazole energetic material, characterized in that: The method is prepared by any one of claims 1 to 8.

10. A coupled electrolysis system for implementing the preparation method steps described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Hydrogen production method for coupling preparation of azofurazan energetic material based on WS2 / Pt composite catalyst

    CN115821293A